Transformer-Based Multi-Scale Feature Remote Sensing Image Classification Model - Ting Sun; Jun Li; Xiangrui Zhou; Zan Chen (IEEE Access)
To address the challenge of poor classification accuracy due to complex backgrounds, large intra-scale variations, and high inter-scale similarity in remote sensing scene classification (RSSC), we propose a new remote sensing scene classification model called multi-scale dual-branch classification network (MDBC-Net). The model is composed of a Trans-branch and CNN-branch in parallel, which can fully utilize the local attention of the CNN-branch structure and the global attention mechanism of the Trans-branch structure, thereby improving the model’s ability to focus on features of different scales. Due to the complexity of backgrounds in RSSC, we require features at different scales to obtain richer scene information. Thus we design a down-sampling module in the model to obtain multi-scale features. Finally, we adopt the polynomial form of cross entropy for the trained loss function to improve the generalization performance and robustness of the model. Experiments have shown that the model achieves advanced performance on three datasets: NWPU-RESISC45, AID, and UC Served.